PEMBELAJARAN MATEMATIKA PADA LMS CHAMILO UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR SISWA - Dwiki Maulidittya; Ria Sudiana; Aan Subhan Pamungkas (JPPM (Jurnal Penelitian dan Pembelajaran Matematika), 2020)
This research aims to develop content of learning management system (LMS) chamilo based smartphone and computer as a media for learning mathematics and to know effectivity of learning management system (LMS) development in enhances self regulated learning of the students. This research is a research and development (R&D) with ADDIE development models. The steps that have been taken in this research are analysising of school’s condition and finding the potential and problems of learning media, designing learning media in appropiate to the result of analysis, developing the result of design that have been made, implementation of learning media to the masters, they are master of learning media and master of mathematics education, and evaluation of learning media that be feasible according to the masters to students. To see the feasibility of learning media, its did validation first product of learning media. In the implementation step, its did validation that had been made, and there is quality level of learning media based on assessment of learning media : 1) Master of Learning Media obtained a percentage of 84% with a very good category, 2) Master of Mathematics Education obtained a percentage of 91% with a very good category. Effectivity of learning media based on evaluation of learning media by the students, the result are Student’s responses of learning media obtained a percentage of 80,03% with a very good category. Beside it, too see self regulated learning of the students has increase from 54,26%to 72,56%. Therefore, learning media that proved is effective used in learning mathematics to enhance self regulated learning of the students.Keywords: Self Regulated, LMS Chamilo.